Water Retention Functions of Four Nonwoven Polypropylene Geotextiles. Issue 6 (1st January 1997) - Stormont, J.C.; Evans, T.M.; Henry, K.S.
Abstract : The water retention functions of four nonwoven polypropylene geotextiles were measured. Each of the four geotextile types were tested in two conditions: new and cleaned. The water retention functions of each geotextile specimen were found to be hysteretic. The new geotextile specimens always contained more water at comparable suction heads than the cleaned geotextile specimens. At zero suction head, the new specimens approached saturation, whereas the cleaned specimens were less than 20% saturated.